The memory of lavender and sage : a novel - Runyan, Aimie K. (Harper Muse, 2024)
"Bestselling author Aimie Runyan makes her contemporary women's fiction debut with this charming escape into the lavender fields of Southern France and a young woman who discovers her family's secrets and the hope for her own future"--